International Law to Understand Russia's Invasion of Ukraine 2022: Between Self-Defense and Defiance - Sardjana Orba Manullang; Irma Rachmawati Maruf; Hadi Priyono; Tamaulina Br Sembiring; Prasetyono Hendriarto (LEGAL BRIEF, 2022)
This paper's legal review will discuss how to understand the Russian invasion in 2022 from the point of view between self-defense and disobedience to international law. To discuss the above theme, we conducted a series of data source searches on some scientific publications, global politics, international law, and the mass media that seriously discuss the racial conflict with Ukraine. This study uses a phenomenological approach, which is trying to understand international events, complete with the questions of this study. We found information and supporting data by searching on the Google engine or electronically and continued with data analysis with an in-depth evaluation and concluding relevant to the topic of discussion. So, based on the evidence from international reports, we can conclude that international law history on Russia's attack on Ukraine in 2022 is a violation of international law. However, when viewed from a country's defense, its existence, and openness to foreign powers in a neighboring country. Russia, then this is a threat to the safety of secrets in the future.